2023
DOI: 10.1111/andr.13381
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to elevated temperature affects the expression of PIWI‐interacting RNAs and associated transcripts in mouse testes

Abstract: Background: Exposure to heat waves could result in adverse effects on human health, especially in male testicles. PIWI-interacting RNA (piRNA) is a novel type of small non-coding RNA, which can notably impact mRNA turnover and preserve germline maintenance in germline cells. However, piRNA's expression status when adapting to testicular heat stress remains largely unclear. Objectives:To investigate the function and mechanisms of relevant piRNAs during testicular heat stress. Materials and methods:In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Typically, exposure to hot water for over 30 minutes per day can lead to specific damage in the anatomical morphology and sperm quality of the male testis within a week 22 . Previous studies predominantly delved into specific types of sncRNAs, such as microRNA 23 or piRNA 24 , to understand testicular damage induced by heat stress. However, the dynamic alterations within the intricate regulatory network of sncRNAs in the testis under heat stress remain unexplored.…”
Section: Background and Summarymentioning
confidence: 99%
“…Typically, exposure to hot water for over 30 minutes per day can lead to specific damage in the anatomical morphology and sperm quality of the male testis within a week 22 . Previous studies predominantly delved into specific types of sncRNAs, such as microRNA 23 or piRNA 24 , to understand testicular damage induced by heat stress. However, the dynamic alterations within the intricate regulatory network of sncRNAs in the testis under heat stress remain unexplored.…”
Section: Background and Summarymentioning
confidence: 99%
“…In this special issue, we learn about the likely involvement of ADAD2, 33 as well as EXD1 and EXD2 34 in the piRNA biogenesis, and how some piRNAs may change due to heat stress. 35 Finally, we learn that piRNAs seem dysregulated in germ cell tumors, 36 and how piRNAs, as well as other sncRNAs, found in seminal plasma may be used to describe changes in the microbiome when a germ cell tumor develops. 37 Studies in animals have indicated that the sncRNA profile of spermatozoa changes from the caput to the cauda of the epididymis.…”
mentioning
confidence: 99%